2011
DOI: 10.1002/path.2978
|View full text |Cite
|
Sign up to set email alerts
|

Hsa‐miR‐375 is differentially expressed during breast lobular neoplasia and promotes loss of mammary acinar polarity

Abstract: Invasive lobular carcinoma (ILC) of the breast, characterized by loss of E-cadherin expression, accounts for 5-15% of invasive breast cancers and it is believed to arise via a linear histological progression. Genomic studies have identified a clonal relationship between ILC and concurrent lobular carcinoma in situ (LCIS) lesions, suggesting that LCIS may be a precursor lesion. It has been shown that an LCIS diagnosis confers a 15-20% risk of progression to ILC over a lifetime. Currently no molecular test or ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 51 publications
1
62
0
2
Order By: Relevance
“…These results strongly suggested that miR-224 functioned as a tumour suppressor in PCa cells. Downregulation of miR-224 has also been reported in other types of human cancers, including ovarian, lung, and breast cancers, in addition to PCa [17][18][19][20][21]. Additionally, one study has shown that more aggressive PCa is associated with lower expression of miR-224 and that downregulation of miR-224 is associated with biochemical relapse [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results strongly suggested that miR-224 functioned as a tumour suppressor in PCa cells. Downregulation of miR-224 has also been reported in other types of human cancers, including ovarian, lung, and breast cancers, in addition to PCa [17][18][19][20][21]. Additionally, one study has shown that more aggressive PCa is associated with lower expression of miR-224 and that downregulation of miR-224 is associated with biochemical relapse [22].…”
Section: Discussionmentioning
confidence: 99%
“…Improved understanding of ncRNAs is necessary for continued progress in cancer research. MicroRNAs (miRNAs) are endogenous small ncRNA molecules (19)(20)(21)(22) bases in length) that regulate the expression of protein-coding genes by repressing translation or cleaving RNA transcripts in a sequencespecific manner [5]. A significant amount of evidence suggests that miRNAs are aberrantly expressed in many human cancers and play significant roles in the initiation, development, and metastasis of those cancers [6].…”
Section: Introductionmentioning
confidence: 99%
“…16,17,[23][24][25][26][27][28][29][30][31][39][40][41][42] Downregulation of miR-375 has been reported for gastric cancer, cervical cancer, pancreatic ductal adenocarcinoma and hepatocellular carcinoma. 26,27,29,30,[43][44][45] In gastric cancer, ectopic expression of miR-375 in cancer cells reduced cell viability and induced apoptosis by targeting PDK1 and tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein z (YWHAZ).…”
Section: Aberrant Expression Of Mir-375 and Its Target Genes In Othermentioning
confidence: 99%
“…41 miRNA expression profiling in invasive lobular carcinoma of the breast showed that miR-375 was upregulated when compared with normal breast epithelium. 40 Ectopic expression of miR-375 in non-tumorigenic breast epithelial MCF-10 A cells induced loss of cellular organization and a hyperplastic phenotype. 40 In prostate cancer (PC), both deep sequencing and microarray analysis of miRNA expression revealed that miR-375 was significantly upregulated in tumor tissues.…”
Section: Aberrant Expression Of Mir-375 and Its Target Genes In Othermentioning
confidence: 99%
See 1 more Smart Citation